Improved inclined solar water desalination system - Egelio?lu, Fuat; Agboola, Philips Olaleye; Madani, Seyed Saeed (My University, 2013)
The rapid urbanization, industrialization, developments in agriculture and increase in population are responsible for the growing demand of freshwater around the world. In most part of the world, potable water shortage is a growing concern. North Cyprus lack edible water source due to seawater intrusion into its main aquifers due to over withdrawing. In addition, the low precipitation is adversely affecting the surface water sources. Desalination technology can provide a new source of freshwater accessible to the populace for either domestic or agriculture use. The use of convectional desalination technology comes with the growing concern of fossil fuel price fluctuations and the environmental issues. Therefore, solar desalination technology will be one viable option for the freshwater sources in North Cyprus due to the high solar radiation in the area. This study continues a research in the field of solar desalination within the Mediterranean region. The economic and thermodynamics performance of an improved inclined solar water desalination systems were experimentally investigated. The performances of IISWD with 2, 4 and 6 spray jets were studied. In addition, the effect of wick on absorber plate and porous media (wire mesh) on the performance of the system was investigated. The result of the investigation revealed that the introduction of spray jets to inclined solar water desalination was significant. Three different configurations IISWD, IISWDW and IISWDWM were tested. Each of the configurations was tested concurrently with ISWD (a control system without the spray jets) to effectively monitor the contribution of the spray jets. The maximum daily production of ISWD, IISWD, IISWDWand IISWDWM are 3.25 kg/m2 with daily efficiency of 40.10%, 5.46kg/m2 with daily efficiency of 48.30%, 6.41kg/m2 with daily 50.30% efficiency and 3.03 kg/m2 with daily efficiency 32.6% respectively. The distilled water cost price analysis also shows that IISWDW with 2 spray jet is the most economically viable among all the system while the IISWDW with 6 spray jets was the most expensive. ©IDOSI Publications, 2013.
Keywords: Daily production; Edible water; Inclined solar water desalination; Spray jets; Thermal efficiency